KERAGAAN PEMBIAYAAN USAHATANI TEMBAKAU BESUKI Na Oogst - SUGIARTO -; MAT SYUKUR (SOCA: Jurnal Sosial Ekonomi Pertanian, 2005)
The necessity of capital for the community in village, especially for tobacco Besuki NaOogst farmer is very important to sustainable farm. Nevertheless, the problem of lowcapital will always appear to increase farm and income. So that, the research that giveinformation about financing farm performance tobacco Besuki Na Oogst. Research showafter the end PRPTE project, the access of tobacco farmer to get credit which comes fromformal institution financing, in fact that it doesn’t give any credit for tobacco farmer.Besides that, the frequency of borrowing and values are still low. At first, cost oftransaction is expected to become burden for the credit; it doesn’t have any influence to theborrower. It is because the screening, delivery, and the pattern of incentive, alsoenforcement, application form which has been applied by formal financing institution isgood enough and easy to understand by the farmer who wants to access them. Althoughtobacco farmer aspiration to the formal institution financing which is expected withoutdifficult procedure, on time, exact in the quantity but also with requirement for borrowingapplication which is cheap. To make it cheap and easy for farmer to access formalinstitution financing, that will be better if make Micro Finance Institution (LembagaKeuangan Mikro) in the village which can bridge the credit for agriculture. In thiscondition we hope that it can solve the limits of capital and it can increase farm agriculturaland society income.